Tingkat Literasi Digital Mahasiswa Jurusan Ilmu Perpustakaan Dalam Pemanfaatan E-Resources UIN Raden Fatah Palembang - Rhoni Rodin; Ade Dwi Nurrizqi (IAIN Ponorogo, 2020)
This paper aims to analyze the level of digital literacy ability of 2016 Department of Library Science students in utilizing the e-resoures of UIN Raden Fatah Palembang. This research is a descriptive study with a quantitative approach. Data collection methods using questionnaires, observations, and documentation. The population in this study were all library students of 2016. The validity test used the Pearson product moment formula and the reliability test used the Cronbach alpha formula. The results of this study indicate that the Analysis of Digital Literacy Ability in Utilizing e-resoures by 2016 Department of Library Science students of UIN Raden Fatah Palembang is relatively high. The total average value of all sub-variables in this study was 3.95. With a scale of 0.8 the interpretation of the score in this study is 3.4-4.2 = High. The conclusion is that the level of digital literacy ability in the use of e-resoures by Library Science students in 2016 is relatively high.